Students’ mathematical productions in a collaborative professional development program: A powerful but stressful strategy for teachers - Canavarro, Ana Paula (2020)
This study occurred in the context of a national programme that took advantage of collaborative strategies to promote primary teachers’ professional development concerning mathematical teaching. The programme was grounded in teachers’ classrooms and placed great emphasis on teacher collaboration in schools, adopting the analysis of students’ mathematical productions as focus to promote reflection. Our aim is to understand which attitudes teachers identify to have developed from the discussion of their students’ mathematical productions with peers and the teacher educator. From the content analysis of the portfolios of 45 teachers, we concluded that teachers developed diverse attitudes from the analysis of their students’ solutions to problems, most of them contributing to improve their mathematics teaching practices oriented by high learning standards. Attitudes like embarrassment and concern also emerged from teachers that did not feel comfortable with creative and effective solutions of their students. This suggests that this professional development strategy must be used in articulation with others that can foster teachers’ confidence in mathematics.